A systematic analysis of C5ORF46 in gastrointestinal tumors as a potential prognostic and immunological biomarker - Jiang, Yuhong; Wang, Xiaobo; Li, Lun; He, Jun; Jin, Qianqian; Long, Dongju; Liu, Chao; Zhou, Weihan; Liu, Kuijie (Frontiers in Genetics, 2022)
Background Chromosome 5 open reading frame 46 (C5ORF46), or AP-64 or SSSP1, belongs to the family of open reading frame genes and encodes a small exosomal protein. C5ORF46 has been indicated to participate in antibacterial activity and has also been associated with patient prognosis in pancreatic cancer, colorectal cancer, and gastric cancer. Yet, the prognostic and immunological value of C5ORF46 in human gastrointestinal (GI) tumors remains largely unknown. Herein, we aimed at probing into the potential value of C5ORF46 in GI tumor prognosis and immunology. Methods All original data were downloaded from TCGA and integrated via Strawberry Perl (v 5.32.0) and R (v 4.1.1). The differential expression of C5ORF46 was examined with the Oncomine, TIMER, GEPIA, CCLE, HPA and TCGA databases. The effect of C5ORF46 on prognosis and clinical phenotypes was explored via bioinformatics analyses on the TCGA database and GEPIA. We also used the bioinformatics analyses based on the TCGA database to analyze tumor mutational burden (TMB), microsatellite instability (MSI), immune cell infiltration of distinct GI tumors, the correlations between C5ORF46 expression and several immune-related genes. The GSEA enrichment analyses were performed using R cripts on data downloaded from the GSEA website. And the KEGG pathway enrichment analyses were carried out via DAVID website and presented as bubble charts using ShengXinRen online tools. The c-BioPortal database was used to investigate the genomic alterations of C5ORF46. Results We proved that C5ORF46 was highly expressed in tumor tissues compared to normal tissues in human GI tumors. Moreover, it had been observed a strong correlation between C5ORF46 expression levels and patient prognosis, staging, TMB, MSI, and immune cell infiltration. Furthermore, C5ORF46 presented to be an important regulator in the TME and participated in the regulation of cancer immune functions. C5ORF46 also significantly coexpressed with genes regulating inflammation and immune responses. Conclusion C5ORF46 may serve as a biomarker for GI tumor prognosis and immunology. Moreover, C5ORF46 could be a novel target for gastrointestinal cancer immunotherapy.